Constructing Eco-Islamic University Model: Strategies for Pesantren-Based Higher Education - Rahmawati, Nur Laila; Asnawi, Asnawi; Anis Afifah; Rahmawati, Fatya Nia; Eryul Mufidah (Scidac Plus, 2026)
Bojonegoro faces a critical paradox: it serves as a national energy and extractive-industry hub, yet remains highly vulnerable to ecological disasters such as floods, landslides, and droughts. Despite this alarming condition, Pesantren-based higher education institutions which act as the moral and intellectual foundation for local communities currently lack a comprehensive educational model that integrates Islamic values with a strategic responsiveness to the environmental crises caused by these extractive industries. Therefore, this study aims to construct the